Exchange Rates and Monetary Policy - Vania Stavrakeva; Jenny Tang (Federal Reserve Bank of Boston, 2015)
In this paper we confront the data with the financial-market folk wisdom that monetary policy is one of the key drivers of nominal exchange rates. Focusing on measures of conventional and unconventional monetary policy, we find that monetary policy surprises and changes in expectations about future monetary policy can explain a sizable fraction of the variation in exchange rate changes for certain currency pairs. However, our results show that expected excess returns account for most of this variation. We also find that the importance unconventional monetary policy plays for explaining exchange rate changes is larger in the period since the United States hit the zero lower bound in December 2008. In contrast, the importance of conventional monetary policy is lower during this period due to a decrease in the volatility of monetary policy surprises. Meanwhile, the marginal response of exchange rate changes relative to conventional policy surprises actually has strengthened due to a change in the relationship between these surprises and expected excess returns.
Keywords: E43; F31; G12; G15; 330